Creation of Make-Up Tutorial Video (Body Painting) Based on 3D Warok Boy Character to Introduce Traditional Culture - Basri, Syaiful Qadar; Yanuartuti, Setyo; Sasanadjati, Jajuk Dwi; Akbar, Syekhfani Alif (Proceeding of International Joint Conference on UNESA, 2025)
Reog Ponorogo is a work of traditional art (performance art) that is full of aesthetics. Reog art consists of the Dhadhak Peacock, Bujangganong, Jathilan, Klono Sewandono and Warok dances. The figure of Warok in the Reog tradition is currently problematic because the figure of Warok who used to serve as a shield for the Reog community has now changed his role to become a dancer like a wayang orang warrior dancer. This shift in Warok’s function. This research focuses on the revitalization of the Warok figure or figures. Warok is one of the dancers in the art of Reog. With previous depictions of Warok characters in the world of performances, sometimes we are asked to present figures who are closer to the Warok character, even though in reality quite a few dancers or warok roles are played by players who do not match the character (body, face and posture) of Warok. This phenomenon encouraged researchers to create video tutorials for Warok character make-up (body painting) based on 3D make-up as an effort to introduce traditional cultural values in 5.0 Era. The aim of this research is to create a video tutorial for Warok character make-up (body painting) based on 3D make-up. The research method uses the Four D research and development (R&D) model, which is collaborated with the art creation method. Data collection techniques and data analysis techniques use qualitative and quantitative techniques. The result of this research is that the presence of 3D-based character make-up videos can attract the younger generation to learn and explore Reog art.